PERAN GURU PENDIDIKAN KEWARGANEGARAAN DALAM MEMBANGUN KARAKTER KEPEMIMPINAN PESERTA DIDIK - Aryanti Dwi Untari; Yayang Siska Restu (Pro Patria: Jurnal Pendidikan, Kewarganegaraan, Hukum, Sosial, dan Politik, 2019)
This research is based on the background of the facts in the field. Researchers see that there is a moral decline in students, such as dressing not in accordance with the rules, playing phones and the internet during the lesson, dating, truant when the KBM process takes place. Thus the behavior of these conditions can affect the leadership character of students, so it has a lot of influence on students' personality development including: communication skills with others, emotional conditions, polite behavior and decreased sense of responsibility. Based on these circumstances researchers are interested in conducting a qualitative research using descriptive methods. This study aims to find out, analyze and describe the role of the teacher of citizenship education in building the leadership character of students in SMA Negeri 1 Ciomas. data collection techniques using interviews, observation and documentation. Data validity techniques here use triangulation. Data analysis techniques use data reduction, data presentation and data conclusions. The results of this study are (1) the role of Civics Education teachers in building the leadership character of students in SMA Negeri 1 Ciomas is exemplary, inspirers, motivators, dynamicators and evaluators. (2) The behavior of leadership characters reflected in the students of SMA Negeri 1 Ciomas is faith and piety to God Almighty, fair, considerate, interdependent, decision makers, good listeners. (3) Obstacles to Citizenship Education Teachers in building leadership character in SMA Negeri 1 Ciomas are internal factors and external factors. Internal factors consist of factors from students 'self such as lack of students' awareness of responsibility. While external factors are environmental factors such as students truant during class hours and family factors get less attention from parents.